Insights in the Architecture of Silicon‐Based Plasma Polymers Using Partial Network Ethanolysis Combined with Electrospray Tandem Mass Spectrometry1. Issue 3 (15th January 2013) - Fouquet, Thierry; Petersen, Julien; Ziarelli, Fabio; Bour, Jérôme; Toniazzo, Valérie; Ruch, David; Charles, Laurence
Abstract Thin films obtained upon plasma polymerization of D4 and HMDSO precursors at atmospheric pressure are submitted to controlled ethanolysis to produce oligomers amenable to electrospray mass spectrometry. When using high resolution mass spectrometry to assess their elemental composition and tandem mass spectrometry to characterize their end‐groups, a whole set of ethanolysis products is identified, from which the network connectivity in the original film can be reconstructed. Ethanolysis products of ppD4 and ppHMDSO exhibit the same structural features composed of linear and cross‐linked PDMS moieties, the extent of cross‐linking reflecting the inorganic character of the film. Oligomers originally embedded in the solid network and released as intact species upon its dissolution are also observed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>